EFFECT OF PAPAYA SEEDS ON TOTAL BODY WEIGHT IN FEMALE RABBITS - Masood Ahmed Unarl, Noreen Irum2,Farzana Memon , Barkat sheik4, Gotam Kuma/Reh Naz sheikh6, Ramesh Kumar, Tanwani,lkram tunio (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Introduction: Papaya seeds have been used since ancient times in folklore medicine for treatment of various diseases; nowadays these are researched in a scientific way to standardize their beneficial medicinal and nutritional properties. Seeds contain many bio-active ingredients. Normally, seeds are wasted in spite of their nutraceutical values. This study will help to save the wastage of papaya seeds. This study was planned to assess the pharmacological aspects of seeds of Papaya seeds on total body weight. Objective: to determine the effects of papaya seeds on total body weight in female rabbits. Design of study: Experimental study. Place & Duration: Animal House, Department of Pharmacology and Therapeutics, Peoples University of Medical and Health Sciences for Women Nawabshah-SBA, from Dec 2017 to May 2018. Materials and Methods: For this study thirty adult and healthy female rabbits were selected and subdivided into two groups, Group X (Control) n=l5, given only fresh hay & water and Group Y (study) n=15, given papaya seeds powder as dose of 500mg once a day along with fresh hay & water provided nd libituin, then total body weight were measured on Day 0, 15, 30, 45 & 60. Results: Papaya seeds decreased the total body weight of Group-Y (study) rabbits from mean 2.49 kg to 1.67 kg on Day-60 of study (p<0.001). Conclusion: Papaya seeds have the promising pharmacological effect in reduction of total body weight, without any significant side effects. Still sophicated scientific research is required to prove that chemical compound which causes the weight loss.